2019
DOI: 10.1186/s41983-019-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein A1: a predictor and prognostic biomarker in acute ischemic stroke

Abstract: Background: The apolipoprotein A1 level is recognized as a better indicator of cardiovascular disease than other cholesterol measures. Objectives: To assess the serum level of ApoA1 in acute stroke patients and correlate it with the degree of vessel stenosis, stroke severity, prognosis, and functional outcome. Patients and methods: We prospectively included 60 patients with first-ever cerebrovascular ischemic stroke, and they were matched with 30 healthy individuals matched in age and sex. Patients' neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Apolipoprotein A1 (APOA1) is a major protein component of the high-density lipoprotein (HDL) and exhibits anti-inflammatory and antioxidant effects, hence playing an important role in the protection of the vascular system against oxidative stress. Studies have shown that the levels of APOA1 decrease in patients with stroke and/or infection [ 30 ]. Similarly, decreased levels of APOA1-UP, as a novel biomarker have been reported to have a high sensitivity (91%) and specificity (97%) for the prediction of IS, nominating it as a promising independent predictor of IS [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apolipoprotein A1 (APOA1) is a major protein component of the high-density lipoprotein (HDL) and exhibits anti-inflammatory and antioxidant effects, hence playing an important role in the protection of the vascular system against oxidative stress. Studies have shown that the levels of APOA1 decrease in patients with stroke and/or infection [ 30 ]. Similarly, decreased levels of APOA1-UP, as a novel biomarker have been reported to have a high sensitivity (91%) and specificity (97%) for the prediction of IS, nominating it as a promising independent predictor of IS [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apolipoprotein A1 (ApoA1) is a protein component of high-density lipoprotein (HDL) and is involved in the transfer of excessive cholesterol from peripheral cells to the liver. Aside from its atheroprotective properties, apoA1 also contains anti-inflammatory and antioxidant properties (53). A previous study found that low amounts of apolipoprotein A1 and high amounts of apolipoprotein B were associated with an increased risk of cerebrovascular stroke and cardiovascular diseases (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its atheroprotective properties, apoA1 also contains anti-inflammatory and antioxidant properties (53). A previous study found that low amounts of apolipoprotein A1 and high amounts of apolipoprotein B were associated with an increased risk of cerebrovascular stroke and cardiovascular diseases (53)(54)(55)(56). High levels of high-density lipoprotein (HDL) cholesterol significantly reduce the risk of stroke (57).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, APOA-1 functions as an antioxidant and an anti-inflammatory (Georgila, Vyrla, & Drakos, 2019). APOA-1-related studies have illustrated that APOA-1 levels can be employed as a predictor and prognostic tool in ischemic stroke patients (Eldeeb et al, 2020).…”
Section: Introductionmentioning
confidence: 99%